The Molecular Epidemiology and Evolutionary Dynamics of Influenza B Virus in Two Italian Regions during 2010–2015: The Experience of Sicily and Liguria - Tramuto, Fabio (Int J Mol Sci, 2016)
Molecular epidemiology of influenza B virus remained poorly studied in Italy, despite representing a major contributor to seasonal epidemics. This study aimed to reconstruct the phylogenetic relationships and genetic diversity of the hemagglutinin gene sequences of 197 influenza B strains circulating in both Southern (Sicily) and Northern (Liguria) Italy between 2010 and 2015. Upper respiratory tract specimens of patients displaying symptoms of influenza-like illness were screened by real-time RT-PCR assay for the presence of influenza B virus. PCR-positive influenza B samples were further analyzed by sequencing. Neighbor-joining phylogenetic trees were constructed and the amino-acid alignments were analyzed. Phylogenetic analysis showed clusters in B/Victoria clade 1A/1B (n = 29, 14.7%), and B/Yamagata clades 2 (n = 112, 56.8%) and 3 (n = 56, 28.4%). Both influenza B lineages were found to co-circulate during the study period, although a lineage swap from B/Victoria to B/Yamagata occurred in Italy between January 2011 and January 2013. The most represented amino-acid substitutions were N116K in the 120-loop (83.9% of B/Yamagata clade 3 strains) and I146V in the 150-loop (89.6% of B/Victoria clade 1 strains). D197N in 190-helix was found in almost all viruses collected. Our findings provide further evidence to support the adoption of quadrivalent influenza vaccines in our country.